L’emigrazione degli ebrei dall’Europa orientale all’Australia nel periodo interbellico - Giuseppe Motta (Diacronie. Studi di Storia Contemporanea, 2016)
The article is focused on the Jewish emigration from Eastern Europe in the years between the first world war and the Thirties. In this context, the conflict and the rise of Nazism contributed to foster a substantial flow of Jewish refugees and migrants, who left their places of residence and moved to Europe, America or even to Australia. In these localities, anyway, the emigrants would find difficult conditions and their arrival would cause tensions and discriminations. Under this perspective, the Australian case is very meaningful in order to understand the stereotypes and bias that have always accompanied the history of migrations, also in some very special cases such as the Jewish one.